ROTATIONAL SPECTRA OF RARE-GAS NITRIC-OXIDE VANDERWAALS MOLECULES .1. THEORY OF THE ROTATIONAL ENERGY-LEVELS - Mills, P; Western, C; Howard, B (1986)
A new Hamiltonian is presented for the analysis of the spectra of open-shell van der Waals molecules with a nonlinear geometry. The theory is similar to that already developed for linear molecules with orbital angular momentum but generalized to asymmetric tops where there is only a slight quenching of the orbital angular momentum. The resulting energy levels show a number of novel features including a rapid variation with angular geometry. Both fine structure and hyperfine effects are considered. © 1986 American Chemical Society.